2022
DOI: 10.1371/journal.ppat.1010231
|View full text |Cite
|
Sign up to set email alerts
|

MAVS mediates a protective immune response in the brain to Rift Valley fever virus

Abstract: Rift Valley fever virus (RVFV) is a highly pathogenic mosquito-borne virus capable of causing hepatitis, encephalitis, blindness, hemorrhagic syndrome, and death in humans and livestock. Upon aerosol infection with RVFV, the brain is a major site of viral replication and tissue damage, yet pathogenesis in this organ has been understudied. Here, we investigated the immune response in the brain of RVFV infected mice. In response to infection, microglia initiated robust transcriptional upregulation of antiviral i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…Intriguingly, we found that in Mavs -/- mice, infected hearts display similar levels of Isg15 compared to WT, suggesting that other pathways may also contribute to IFN-I response in cardiac tissue. This has been observed for Rift Valley fever virus-infected brains, in which no differences in the global induction of the IFN-I signaling between Mavs -/- and WT were observed by bulk RNA-seq (Hum et al, 2022). However, differences in the IFN-I signaling have been observed by single-cell RNA seq (Hum et al, 2022), suggesting heterogeneity in the viral RNA sensing and activation of downstream pathways between different cell types.…”
Section: Discussionmentioning
confidence: 69%
“…Intriguingly, we found that in Mavs -/- mice, infected hearts display similar levels of Isg15 compared to WT, suggesting that other pathways may also contribute to IFN-I response in cardiac tissue. This has been observed for Rift Valley fever virus-infected brains, in which no differences in the global induction of the IFN-I signaling between Mavs -/- and WT were observed by bulk RNA-seq (Hum et al, 2022). However, differences in the IFN-I signaling have been observed by single-cell RNA seq (Hum et al, 2022), suggesting heterogeneity in the viral RNA sensing and activation of downstream pathways between different cell types.…”
Section: Discussionmentioning
confidence: 69%
“…Given the stark differences in survival between the genotypes after footpad infection, we infected a cohort of mice intranasally with 20 PFUs of RVFV. Infection through the intranasal route is thought to facilitate direct brain infection ( 25 , 26 ). Resulting data revealed that there were no differences in survival between Lrp f/f and Lrp1 f/f Alb-Cre mice ( P = 0.92) following intranasal infection (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, early activation of IFNAR signaling in the glomerular layer of the olfactory bulb seems to be critical for the control of viral replication [ 38 ]. The IFN-I response and cytokine expression of RVFV-infected microglia are largely dependent on RIG-I-like receptors (RLR) signaling via mitochondrial antiviral-signaling protein (MAVS), whereas RNA sensing by toll-like receptors (TLRs) only plays a minor role [ 56 ]. MAVS −/− mice intranasally infected with 5x10 5 PFU of the RVFV MP12 vaccine strain showed high levels of viral RNA inside the brain, which was associated with increased T and NK cell infiltration but an impaired T cell activation [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IFN-I response and cytokine expression of RVFV-infected microglia are largely dependent on RIG-I-like receptors (RLR) signaling via mitochondrial antiviral-signaling protein (MAVS), whereas RNA sensing by toll-like receptors (TLRs) only plays a minor role [ 56 ]. MAVS −/− mice intranasally infected with 5x10 5 PFU of the RVFV MP12 vaccine strain showed high levels of viral RNA inside the brain, which was associated with increased T and NK cell infiltration but an impaired T cell activation [ 56 ]. Functional NK cells, macrophages and lymphocytes seem to be essential for RVFV clearance [ 37 ].…”
Section: Discussionmentioning
confidence: 99%